A Consensus Model for Coastal Potential- Conflict Management: The Case of Pangkung Tibah Village, Bali - Ni Ketut Agusintadewi; I Gde Putu Bayu Raka Purba; I Gusti Ngurah Anom Rajendra (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
The tourism development of the Pangkung Tibah Village coastal area has reportedly caused various changes in the functions of lands. These changes have led to potential conflicts among the involved actors, who have different interests, indicating the necessity for problem-solving efforts. Potential conflicts should be addressed early to prevent them from developing into bigger conflicts. The results of this study may be used as a guideline for developing policies to prevent potential conflicts. The study aimed to: (1) identify the characteristics of the potential conflicts in the Pangkung Tibah Village coastal area, (2) carry out an analytical mapping of the potential conflicts, and (3) formulate a consensus model for the management of the potential conflicts by maximizing the role of the local community. The participatory rural appraisal (PRA) approach was used to identify and conduct an analytical mapping of potential conflicts in the Pangkung Tibah Village coastal area. The findings revealed that due to the vulnerability of this coastal area to damages, interventions should be controlled by direct action that is supported by formal and customary laws. Regarding the identification of the actors, causes, and types of differences in this study, an analytical mapping was conducted, with the potential conflicts being categorized into three levels: ‘mild’, ‘moderate’, and ‘severe’. These levels were determined based on the nature of their relationships with the three categories of sustainable development. In conclusion, a consensus model is proposed as a solution to manage the existing potential conflicts in the coastal area of Pangkung Tibah Village based on the local community and stakeholders’ participation in order to well manage the social, economic, and environmental aspects towards sustainable development.